2019
DOI: 10.1371/journal.pone.0225931
|View full text |Cite
|
Sign up to set email alerts
|

Erastin, a ferroptosis-inducing agent, sensitized cancer cells to X-ray irradiation via glutathione starvation in vitro and in vivo

Abstract: High concentrations of antioxidants in cancer cells are huge obstacle in cancer radiotherapy. Erastin was first discovered as an inducer of iron-dependent cell death called ferroptosis accompanied by antioxidant depletion caused by cystine glutamate antiporter inhibition. Therefore, treatment with erastin is expected to potentially enhance cellular radiosensitivity. In this study, we investigated the influence of treatment with erastin on the radiation efficiency against cancers. The clonogenic ability, glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 45 publications
(43 reference statements)
4
65
0
1
Order By: Relevance
“…As an inducer of ferroptosis, erastin was used to evaluate its influence on the development and progression of HCC [ 37 ]. The chemical formula of erastin was showed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an inducer of ferroptosis, erastin was used to evaluate its influence on the development and progression of HCC [ 37 ]. The chemical formula of erastin was showed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the abovementioned drugs RSL3 and erastin, the two main ferroptosis inducers have been used in a variety of tumor models in vitro [114,115]. Both drugs, however, do not meet the pharmacokinetic standards for in vivo application and need to be further optimized for clinical application [116].…”
Section: Ferroptosis Is a New Promising Target For Cancer Treatmentmentioning
confidence: 99%
“…Inhibition of erastin on the proliferation and tumorigenesis of HCC and its possible molecular mechanism As an inducer of ferroptosis, erastin was used to evaluate its in uence on the development and progression of HCC [37].The chemical formula of erastin was showed in Figure 10A. Performing the CCK-8 assay, we found that erastin treatment inhibited cell proliferation in a dose-dependent manner ( Figure 10B-C).…”
Section: Internal and External Validation Of The Expression Patterns mentioning
confidence: 95%